1996
DOI: 10.1074/jbc.271.10.5901
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Subtype of the Prostacyclin Receptor Expressed in the Central Nervous System

Abstract: By use of several prostacyclin analogs and an in vitro autoradiographic technique, we have found a novel subtype of the prostacyclin receptor, one having different binding properties compared with those of the known prostacyclin receptor in the rat brain. Isocarbacyclin, which is a potent agonist for the known prostacyclin receptor, had high affinity for the novel subtype (dissociation constant (K d ) of 7.8 nM). However, iloprost, which is usually used as a stable prostacyclin analog, showed low affinity bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 36 publications
(36 reference statements)
4
75
1
Order By: Relevance
“…This elevated dopamine metabolism, but not the increase in the tyrosine hydroxylase activity, was reversed by subchronic treatment with the Cox-2 inhibitor celecoxib. Previous reports demonstrated that prostaglandins influence the activity of excitatory neurons and monoaminergic neurons (Takechi et al, 1996;Oida et al, 1997;Nakamura et al, 2001;Matsuoka et al, 2005;Sang et al, 2005). Given the defined roles of EGF and prostaglandin, we speculate that EGF may increase dopamine synthesis and prostaglandins may enhance its release.…”
Section: Table 2 Effects Of Egf Infusion and Celecoxib On Tyrosine Hmentioning
confidence: 64%
“…This elevated dopamine metabolism, but not the increase in the tyrosine hydroxylase activity, was reversed by subchronic treatment with the Cox-2 inhibitor celecoxib. Previous reports demonstrated that prostaglandins influence the activity of excitatory neurons and monoaminergic neurons (Takechi et al, 1996;Oida et al, 1997;Nakamura et al, 2001;Matsuoka et al, 2005;Sang et al, 2005). Given the defined roles of EGF and prostaglandin, we speculate that EGF may increase dopamine synthesis and prostaglandins may enhance its release.…”
Section: Table 2 Effects Of Egf Infusion and Celecoxib On Tyrosine Hmentioning
confidence: 64%
“…The precise mechanisms of the neuroprotective effects of TTC-909 are not clear. A novel prostacyclin receptor showing high affinity to TEI-7165 has been detected in a variety of brain regions, such as thalamus, lateral septal nucleus, hippocampus cerebral cortex, striatum and dorsal cochlear nucleus (28). This novel subtype was shown to exist on neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, knowledge concerning the specific function of PGI 2 in the human brain is limited. Indeed, the assumption that PGI 2 is synthesized in brain tissue in vivo is based on observations in primary culture of astrocytes and meningeal cells (Murphy et al ., 1985) as well as of the expression of PGI 2 receptor (PI) in the rodent brain (Oida et al ., 1995; Takechi et al ., 1996). Siegle et al .…”
Section: Discussionmentioning
confidence: 99%